(untitled) (Sociologisk Forskning, 2019)
The logics of capitalist temporality dominate western society today. Drawing on Barbara Adam’s work, we explore two important dimensions of this dominant temporality. Standardised and abstract clock time involves a detachment from seasons and the life-world, closely related to the commodification of time exemplified by expressions like ”time is money”. Many initiatives attempt to challenge the dominance of capitalist temporality, amongst which we present: (1) worker cooperatives that organize work and its temporality as alternatives to capitalism; and (2) timebanks where people exchange services with each other based on time rather than money. We investigate how these illustrative examples differ from the dominant capitalist temporality, and in what ways they depend on the same logic that they resist. The analysis shows that the initiatives divert from the dominant temporality in important aspects, but also reproduce it in other ways. Thereby, this article contributes to theorizing resistance in connection to time and temporality, and gives insights in the potential and elusiveness of constructive resistance to dominant temporality.